The Implementation of Artificial Intelligence, Chatgpt, And Critical Thinking Method for Academic Endeavors at Theological Higher Education - Tolop Oloan Marbun (Jurnal Didaskalia, 2023)
The primary aim of this research is to incorporate the use of Artificial Intelligence, ChatGPT, and the Critical Thinking Method to enhance academic endeavors. Employing Artificial Intelligence and ChatGPT in academic work offers advantages to educators and students. Although educators and students are still required to verify data and references independently, the use of Artificial Intelligence and ChatGPT enables the quick and precise presentation of information. Therefore, it is essential to integrate the Critical Thinking methodology with the utilization of ChatGPT and Artificial Intelligence. Verifying and validating data improves the credibility of the knowledge acquired by both professors and students. The research methodology employed in this project involved library research, where the author collected primary and secondary data. Subsequently, content analysis methodology was applied, and the data was presented descriptively. The study results indicate that the implementation of Artificial Intelligence, ChatGPT, and the Critical Thinking method has enhanced the quality of academic work produced by educators and students. Furthermore, this combination can expedite the production of scholarly articles. When engaging in academic research, educators and students should adhere to the guidelines on Artifact Intelligence and ChatGPT policies.